The Effect of Peppermint Aromatherapy and Acupressure on Point P6 to Reduce the Incidence of Emesis Gravidarum - Salma Rahmadania Salma; Maryam Syarah; Shinta Mona Lisca (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2026)
Pregnant women who experience nausea and vomiting during the first trimester are said to have emesis gravidarum. Changes in progesterone and estrogen levels are considered contributing factors to this condition. Complementary therapies such as pericardium acupressure and peppermint aromatherapy can be used to treat emesis gravidarum. The purpose of this study was to evaluate the effects of pericardium acupressure and peppermint aromatherapy on nausea and vomiting experienced by first-trimester pregnant women in Ciadeg Village. The quasi-experimental process used a two-group pre-test and post-test design. The overall study sample consisted of 32 first-trimester pregnant women respondents who experienced emesis gravidarum. Peppermint aromatherapy and pericardium acupressure had a significant impact, according to bivariate analysis using the Wilcoxon test, with a p-value of 0.000 <0.05. According to the study findings, the average emesis gravidarum score was 8.81 before receiving peppermint aromatherapy and 4.63 after the intervention. The average emesis gravidarum score was 7.87 before pericardium acupressure point 6, and 5.12 after the intervention. Therefore, this complementary therapy can significantly reduce the incidence of emesis gravidarum in first trimester pregnant women in Ciadeg Village in 2025. The goal is to reduce emesis gravidarum and improve maternal understanding of emesis gravidarum treatment.